THE RELATIONSHIP BETWEEN THE ROLE OF LEADERSHIP AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. COSMAX INDONESIA - Dian Esterlita Silitonga; Hotner Tampubolon; Simanjuntak, Ramot P. (Fundamental Management Journal, 2022)
The research aims to determine how the relationship between the role of leadership and work motivation on improving employee performance at PT. Cosmax Indonesia. The data employed in this study are both primary and secondary data, and it is a quantitative study. Primary data is done by distributing questionnaire statements to respondents with a sample of 53 employees, and secondary data through company profiles, books and journals that support the research. The analytical method used is non-parametric statistics using SPSS software. The hypothesis used to determine the relationship between variables is Spearman rank correlation analysis and t test.Based on the results of the study, it shows that there is a significant positive relationship between the role of leadership on improving employee performance as shown by the obtained t count (3.784) > t table (2.021), with a spearman rank correlation value of 0.468. There is a significant positive relationship between work motivation and employee performance as shown by the obtained t count (3.772) > t table (2.021), with a Spearman rank correlation value of 0.467.The author's suggestions regarding the role of leadership, leaders in companies need to improve their role in providing motivation, have a high participation spirit to help employees and be open to receiving ideas and input from employees. Regarding work motivation, companies need to improve again in providing work motivation to employees by providing training and career development to employees, giving awards for the work obtained by employees, and paying more attention to the work climate in the company. Regarding employees, it is good for employees in the company to be able to work together and help each other in doing work in order to achieve company goals.Keyword : Leadersship,Work